Managerial School Principals in Improving the Quality of Education Through the Driving School Program - Putri, Cilsilia Anindi (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2017)
This research aims to describe the managerialism of school principals in improving the quality of education through the Driving School Program in State Elementary Schools 1/IV, Jambi City. This research uses a qualitative approach with a case study type of research. The informants in this research were the school principal, class I teacher and class IV teacher who taught using the Educational Unit Operational Curriculum. The data collection techniques used were through observation, interviews and documentation. The data obtained was analyzed in stages, first data reduction, second data presentation, third drawing conclusions and verification. The results of the research show that there are four stages in the management of school principals in improving the quality of education through the Driving School Program at State Elementary School 1/IV in Jambi City, namely: (1) planning stage. (2) organizing stage. (3) briefing stage. (4) supervision stage. From the research results it can be concluded that in carrying out his managerial function the principal of Jambi City State Elementary School 1/IV has tried his best to improve the quality of school education. One of the efforts made is through the Driving School Program.